Affinin, Isolated from Heliopsis longipes, Induces an Antihypertensive Effect That Involves CB1 Cannabinoid Receptors and TRPA1 and TRPV1 Channel Activation - Luz-Martínez, Beatriz A.; Marrero-Morfa, Dailenys; Luna-Vázquez, Francisco J.; Rojas-Molina, Alejandra; Ibarra-Alvarado, César (Planta Medica, 2024)
In previous studies, we demonstrated that the ethanolic extract of Heliopsis longipes roots and its main alkamide, affinin, elicit a vasorelaxant effect through a mechanism involving activation of the gasotransmitter pathways and stimulation of cannabinoid type 1 receptors and transient receptor potential ankyrin 1 and transient receptor potential vanilloid 1 channels. However, it has not yet been demonstrated whether the EEH and affinin are capable of lowering high blood pressure. Therefore, the aim of the present study was to determine the effect of the oral administration of the EEH and affinin on the systolic blood pressure of NG-nitro-L-arginine methyl ester-induced hypertensive rats and to explore the participation of cannabinoid receptors and transient receptor potential channels in the mechanism of action of this alkamide. Our results showed that the ethanolic extract of H. longipes and affinin significantly lowered systolic blood pressure and induced an improvement in endothelial function, which is associated with increased serum nitric oxide levels. Inhibition of cannabinoid type 1 receptors by rimonabant (3 mg/kg), transient receptor potential ankyrin 1 channels by HC-030031 (8 mg/kg), and transient receptor potential vanilloid 1 channels by capsazepine (5 mg/kg) significantly decreased the antihypertensive effect induced by affinin, suggesting that the blood pressure-lowering effect of this alkamide involves activation of cannabinoid type 1 receptors and transient receptor potential ankyrin 1 and transient receptor potential vanilloid 1 channels.
Keywords: affinin; Asteraceae; CB1 cannabinoid receptor; Heliopsis longipes; hypertension; TRP channels